Suspected Hepatotoxicity With a Supercritical Carbon Dioxide Extract of Artemisia annua in Grapeseed Oil Used in New Zealand - Savage, Ruth L.; Hill, Geraldine R.; Barnes, Joanne; Kenyon, Susan H.; Tatley, Michael V. (Frontiers in Pharmacology, 2019)
Abstract A case series of hepatotoxicity associated with an extract of Artemisia annua L. was identified through the New Zealand spontaneous adverse drug reaction reporting system. A. annua extract, produced using a supercritical carbon-dioxide extraction method and formulated with grapeseed oil, has been marketed in New Zealand as a natural product for joint health. As of 31 January 2019, the New Zealand Pharmacovigilance Centre had received 29 reports of hepatic adverse reactions occurring in patients taking A. annua extract in grapeseed oil. The case reports were assessed for patient and adverse reaction characteristics, patterns of A. annua extract use and causality (based on the WHO-UMC system for standardised case causality assessment). Patients were aged 47 to 93 years (median 67). Time to onset of hepatotoxicity from starting A. annua extract was 7 days to approximately 12 months in the 23 reports with this information. Nineteen of these reports indicated onset within 12 weeks. A. annua extract was the sole suspect medicine in 27 reports. A few patients had possible predisposing conditions. Twenty-seven patients were reported to have recovered or improved on stopping A. annua extract. Nine patients required hospital admission. The pattern of hepatic injury varied. Jaundice, often with pruritus and dark urine, was experienced by 16 patients. We assessed the case series using the Bradford Hill principles for causality assessment and concluded that a causal association between A. annua extract and hepatotoxicity is likely.